نمذجة نظام مانع الانغلاق الدوراني باستخدام شبكات بتري عالية المستوى - شيحا, بلال; البستاني, حسن; عبد اللطيف, ميس (Latakia University Journal -Engineering Sciences Series, 2019)
أدى استخدام نظام مانع الانغلاق الدوراني (Anti-Lock Braking System) في المركبات إلى زيادة نسبة الأمان على الطرقات بشكل ملحوظ، وذلك بمنع الإطارات من الانغلاق أثناء عملية الفرملة من خلال التحكم بقيمة الضغط المطبق على كل إطار، ومن ثمَّ تمكين السائق من الاستمرار بالتحكم بالمركبة وتقليل المسافة اللازمة للوقوف ولاسيما على السطوح الزلقة . تم في هذه المقالة إجراء دراسة رياضية لكل من المركبة والإطار لمعرفة القوى المؤثرة في كل منها، ويعتبر الجديد في هذه الدراسة استخدام شبكات بتري عالية المستوى وكفرع منها شبكات بتري الملونة (Coloured Petri Nets) كأداة نمذجة لبناء نموذج لنظام مانع الانغلاق الدوراني، ثم أجرينا تحليلاً لنتائج عملية المحاكاة ودراسة تغير بارامترات النظام وتأثيرها في أدائه. The use of Anti-Lock Braking System (ABS) in vehicles led to increase safety on the roads significantly, by preventing wheels from locking up during braking by controlling the values of applied pressure on each wheel, thus enabling the driver to keep control of the vehicle and reduce the stopping distance, especially on the slippery surfaces. In this article a study of the forces acting on both the vehicle and the wheel is applied. The new element in this study is the use of High Level Petri Nets and its branch Coloured Petri Net as a modeling tool to build a model of the Anti-Lock Braking System, and then we analyze the results of the simulation to study the change of the system’s parameters and how they affect the system’s performance.